Splenectomised and spleen intact Aotus monkeys'immune response to Plasmodium vivax MSP-1 protein fragments and their high activity binding peptides. (2003)
Two E. coli expressed recombinant polypeptides (rPvMSP-114 and rPvMSP-120) contained in the 33 kDa fragment, located within Plasmodium vivax merozoite surface protein (PvMSP-1) 42 kDa C-terminal region, and a cocktail of high reticulocyte binding synthetic peptides located within these fragments, were evaluated for immunogenicity and protective immune responses in splenectomised and spleen intact Aotus nancymaae monkeys. Thirty splenectomised monkeys who had been previously immunised with either rPvMSP-114, rPvMSP-120, or a mixture of both recombinant fragments were intravenously challenged with the heterologous P. vivax VCG-1 strain (as determined by DNA sequencing); full protection was observed in five monkeys and low parasitaemia levels were obtained in eight more monkeys. Splenectomised control monkey group rapidly developed high parasitaemia levels, while no significant parasitaemia was obtained in the non-splenectomised control group. Although PvMSP-1 42 and 33 kDa fragments were recognised by Western Blot and whole parasites by IFAT when tested with immune monkey sera, no correlation between protection and antibody titres by IFAT and ELISA was observed, suggesting that protection is not being solely mediated by a humoral immune response. This data showed that partial protection against a heterologous strain challenge was best achieved when immunising with a rPvMSP-114–rPvMSP-120 mixture (2 were fully protected and 4 with low parasitaemia out of 12) suggesting for the first time, that these fragments could be good candidates for inclusion in a P. vivax multi-stage, multi-antigen vaccine.